PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR - Muhammad Rifqi; Yon Rizal; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2014)
This study aims to determine the effect of learning motivation and learning environments on learning outcomes of economic semester of ten grade student of Madrasah Aliyah Negeri Pringsewu Academic Year 2013/2014. The method used in this research is descriptive approach verification ex post facto and surveys. The population in this study amounted to 235 students and a sample of 148 students. Data were collected through questionnaires and processed by computer through SPSS version 16. The first and second hypotheses testing using simple linear regression formula, while the third hypothesis using multiple linear regression formula. Based on the analysis of the data obtained the following results: (1) There is a positive and significant effect of learning motivation on learning outcomes of economic semester of ten grade student of Madrasah Aliyah Negeri Pringsewu Academic Year 2013/2014. (2) There is a positive and significant effect of learning environments on learning outcomes of economic semester of ten grade student of Madrasah Aliyah Negeri Pringsewu Academic Year 2013/2014. (3) There is a positive and significant effect of learning motivation and learning environments on learning outcomes of economic semester of ten grade student of Madrasah Aliyah Negeri Pringsewu Academic Year 2013/2014. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi belajar dan lingkungan belajar terhadap hasil belajar ekonomi siswa kelas X Madrasah Aliyah Negeri Pringsewu Tahun Pejaran 2013/2014. Metode yang digunakan dalam penelitian ini adalah deskriptif verifikatif dengan pendekatan ex post facto dan survei. Populasi dalam penelitian ini berjumlah 235 siswa dan sampel 148 siswa. Data yang terkumpul melalui angket dan diolah dengan komputer melalui program SPSS versi 16. Pengujian hipotesis pertama dan kedua menggunakan rumus regresi linier sederhana, sedangkan hipotesis ketiga menggunakan rumus regresi linier multiple. Berdasarkan analisis data diperoleh hasil sebagai berikut: (1) Ada pengaruh yang positif dan signifikan motivasi belajar terhadap hasil belajar ekonomi siswa kelas X Madrasah Aliyah Negeri Pringsewu Tahun Pejaran 2013/2014. (2) Ada pengaruh yang positif dan signifikan lingkungan belajar terhadap hasil belajar ekonomi siswa kelas X Madrasah Aliyah Negeri Pringsewu Tahun Pejaran 2013/2014. (3) Ada pengaruh yang positif dan signifikan motivasi belajar dan lingkungan belajar terhadap hasil belajar ekonomi siswa kelas X Madrasah Aliyah Negeri Pringsewu Tahun Pejaran 2013/2014. Kata kunci: hasil belajar, lingkungan belajar, dan motivasi belajar.